Intonationally Marked Sentences with Phraseological Structures: Status and Features (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article is devoted to consideration of sentences that can act as both sentences with phraseological structures and regular ones, depending on the intonation carried out in a particular situation and context. The place of intonationally marked sentences with phraseological structures in the system of phraseological units was determined; their differential features were revealed; there were identified the factors that motivate the potential of initiation of a special type of syntactic homonymy – homonymy of sentences with phraseological structures and regular ones in Ukrainian.
Keywords: intonation; syntactic idiom; sentence with phraseological structure; phraseological unit; the Ukrainian language